Evolutionary development of phonological awareness: How does it relate to reading literacy? - de la Calle, Ana María; Aguilar, Manuel; Navarro, José Ignacio (Revista de Investigación en Logopedia, 2016)
From the Emergent Literacy current it investigates the predictors of reading literacy. One of these predictors is phonological awareness. Our study aims to understand the normal sequence of development in the reading mechanism acquisition finding out the degree of difficulty of various tasks of phonological awareness students and its relationship with later reading literacy, in 126 preliterate. Evaluations were carried out in two stages: 1) Kindergarten of 4 and 5 years of age, and 2) 1st Primary and 2nd Primary; respectively. The instruments used were the Battery Start to Reading (BIL 3-6) and the Test of Reading and Writing in Spanish. The data were submitted to descriptive analysis, correlation analysis, regression analysis and ANOVA; and factor analysis. The results show that the isolate tasks syllables and phonemes with the counting syllables tasks are easier than the syllable omission task and the rhyme task, resulting in the latter more difficult, for pre-readers students. The results support that there is a correlation between the level of reading literacy and the phonological awareness tasks.
Keywords: Phonological awareness; Reading development; Reading literacy.